Impact of Safety Management Practices on Safety Performance in Workplace Environment: A Case Study in Iraqi Electricity Production Industry - Tawfeeq, Omar Munaf; Thiruchelvam, Sivadass A. L.; Bin Zainal Abidin, Izham (Engineering, Technology & Applied Science Research, 2024)
Organizations are becoming more aware of the need to ensure a safe working environment for their staff. Technological advancements and industrial growth have enhanced efficiency, however, they present new challenges and risks for employees. Accidents remain a concern despite International Labor Organization (ILO) guidelines, governmental bodies, and industry institutions promoting workplace safety. Therefore, it is crucial to evaluate the determinants of workplace safety performance, particularly in the electrical power industry. This study formulates a theoretical model to assess the predictors of safety practices of managers and staff in the Iraqi electricity sector, extending the safety climate model with four external constructs and a moderating variable. Data were collected from 374 participants using an online questionnaire and the PLS-SEM method for analysis. The factor loadings exceeded the recommended value of 0.7 and internal consistencies were greater than the threshold value of 0.8. The findings showed that the safety performance in the Iraqi electric power sector is influenced by safety communication, safety policy, safety control, prevention planning, and safety commitment. Safety commitment is affected by safety policy, prevention planning, control, and communication, while safety training and safety control were found to be insignificant. Furthermore, safety communication had the most significant effect. The results of this study provide some theoretical and practical implications for employees’ safety performance toward their overall safety in the electric power industry.